Clinical and Bacterial Characteristics of Klebsiella pneumoniae Affecting 30-Day Mortality in Patients With Bloodstream Infection - Wu, Xingbing; Shi, Qingyi; Shen, Shimo; Huang, Chen; Wu, Hongcheng (Frontiers in Cellular and Infection Microbiology, 2021)
Background There is a paucity of studies using clinical characteristics and whole-genome sequencing together to fully identify the risk factors of patients with Klebsiella pneumoniae (KP) bloodstream infection (BSI). Methods We retrospectively analyzed the clinical and microbiological characteristics of patients with KP BSI. Isolates were processed using Illumina NGS, and relevant bioinformatics analysis was conducted (multi-locus sequence typing, serotype, phylogenetic reconstruction, detection of antibiotic resistance, and virulence genes). A logistic regression model was used to evaluate the risk factors of hosts and causative KP isolates associated with 30-day mortality in patients infected with KP BSI. Results Of the 79 eligible patients, the 30-day mortality rate of patients with KP BSI was 30.4%. Multivariate analysis showed that host-associated factors (increased APACHE II score and septic shock) were strongly associated with increased 30-day mortality. For the pathogenic factors, carriage of iutA (OR, 1.46; 95% CI, 1.11–1.81, p = 0.002) or Kvar_1549 (OR, 1.31; 95% CI, 1.02–1.69, p = 0.043) was an independent risk factor, especially when accompanied by a multidrug-resistant phenotype. In addition, ST11-K64 hypervirulent carbapenem-resistant KP co-harbored acquired blaKPC-2 together with iutA (76.5%, 13/17) and Kvar_1549 (100%, 17/17) genes. Comparative genomic analysis showed that they were clustered together based on a phylogenetic tree, and more virulence genes were observed in the group of ST11-K64 strains compared with ST11-non-K64. The patients infected with ST11-K64 strains were associated with relatively high mortality (47.2%, 7/17). Conclusion The carriage of iutA and Kvar_1549 was seen to be an independent mortality risk factor in patients with KP BSI. The identification of hypervirulent and carbapenem-resistant KP strains associated with high mortality should prompt surveillance.